2018
DOI: 10.2196/resprot.8541
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Training Program Using Cognitive Behavioral Therapy to Enhance Cognitive Flexibility and Alleviate Psychological Distress Among Schoolteachers: Pilot Randomized Controlled Trial

Abstract: BackgroundSchoolteachers are known to be faced with various stresses in their work. A simple, less onerous, and effective intervention technique that can enhance the stress management skills, particularly, cognitive flexibility, of schoolteachers is needed.ObjectiveThis study aimed to determine whether stress management training using a Web-based cognitive behavioral therapy (CBT) program is effective for enhancing the cognitive flexibility of schoolteachers and alleviating their subjective distress.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Evidence on computer‐based interventions shows promising results for the treatment of clinical problems like depression and anxiety disorders (Hedman et al, 2012), eating disorders (ter Huurne et al, 2015), or addictive behaviour (Postel et al, 2010), but also for the treatment of subclinical problems in different population, depending of some characteristics, like the group age (adolescents, young adults or older adults) (Välimäki et al, 2017; Vanoh et al, 2018), or the belonging to a risk profession, like health professionals (Hersch et al, 2016) or teachers (Oishi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on computer‐based interventions shows promising results for the treatment of clinical problems like depression and anxiety disorders (Hedman et al, 2012), eating disorders (ter Huurne et al, 2015), or addictive behaviour (Postel et al, 2010), but also for the treatment of subclinical problems in different population, depending of some characteristics, like the group age (adolescents, young adults or older adults) (Välimäki et al, 2017; Vanoh et al, 2018), or the belonging to a risk profession, like health professionals (Hersch et al, 2016) or teachers (Oishi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were conducted in the UK,14 24–26 seven studies were from the USA,12 13 15 27–30 four from Hong Kong,11 31–33 four studies from Nigeria 34–37. Others were from Spain,38 Australia,39 Netherlands,40 Japan,41 India,42 Germany43 and Poland 44. These studies were published between 1999 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study revealed that individual behavioral factors, such as proper sleep habits and stress coping skills, are important preventative factors for depression. Further, the findings indicated the validity of promoting existing measures to prevent depression among middle-aged residents in Japan, such as providing interventions for reconstructing stress-sensitive cognition, [ 35 ] encouraging help-seeking behavior, [ 36 ] and improving sleep quality. [ 37 ] However, it is difficult to promote these interventions in the community because they can be burdensome for busy middle-aged people.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies that implemented interventions based on cognitive behavioral therapy to reduce stress consisted of 2 hours of group education and 3 months of web-based homework. [ 35 ] For the general, healthy population, attending a group health education class and continuing homework for 3 months would likely be too burdensome to complete the program. Furthermore, while intervention programs to improve SOC are being developed, the current programs still lack sufficient evidence regarding their effectiveness.…”
Section: Discussionmentioning
confidence: 99%